Assessment of The Family Support on The Improvement of Health-Related Quality of Life for Alcoholics and Smokers in Type 2 DM Patients in Makassar Municipality - Syatriani, Sri; Ridwan, Amiruddin; Djaffar, Nurhaedar; Ansariadi, Ansariadi (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2017)
Positive dimensions of family functioning are an important aspect to boost adherence behaviors in diabetic patients in increasing their quality of life, especially for alcoholics and smokers with type 2 DM. Concerning to this issue, this study aims to assess family support on the improvement of health-related quality of life for smokers and alcoholics in type 2 DM patients at coastal areas in Makassar Municipality. The study used a cross-sectional study. Samples were alcoholics and smokers with type 2 DM who stay at coastal areas in Makassar Municipality. Samples were males and total samples were 366 respondents. Data were collected using questionnaires and interview with respondents using the WHO-QoL survey instrument and the questionnaires of smoking habits and habitual consumption of alcohol. Analysis of data used Yates